Assessing Sugarcane Molasses’ Bioactive Compound Content upon Ultrasound-Assisted Hydroethanolic Extraction at Various pH Values - Boukaga Farmani; Miljana Djordjević; Somayeh Mohammadkhani; Marijana Djordjević (Agriculture)
As widely generated by-products with significant bioactive compound content, sugarcane molasses exhibits high potential for valorization. For the purpose of bioactive compound extraction from sugarcane molasses, ultrasound-assisted extraction with various hydroethanolic solvents (0, 2.5, 5, 7.5, and 10% ethanol) at different pH values (4.11, 5.11, 6.11, and 7.11) was examined. In the obtained sugarcane molasses extracts, the content of total phenolics, monomeric anthocyanins, total flavonoids, total tannins, and antioxidant capacity (DPPH) was estimated alongside the determination of molasses’ major components through GC-MS analysis Based on the GC-MS analysis of molasses, sugars and nitrogenous compounds emerged as the most abundant compounds classes. Hydroethanolic solvent of 2.5% at pH 6.11 exhibited the most prominent extraction power regarding total phenolics (22074.98 µg GAE mL−1) and total flavonoids (245.42 µg QE mL−1). Furthermore, extraction with 2.5% hydroethanolic solvent at pH 5.11 displayed the highest total tannins (1177.85 µg CE mL−1). The behavior of monomeric anthocyanins in ultrasound-assisted extraction with hydroethanolic solvent was slightly different, where 2.5% hydroethanolic solvent extracted the highest amount at pH 4.11 (11.1 µg CGE mL−1) and 7.11 (10.68 µg CGE mL−1). The results of the DPPH assay indicated that extracts obtained using 2.5% hydroethanolic solvent at pH 4.11 (68.35%) and pH 5.11 (68.10%) evinced the highest neutralization power against DPPH free radicals. In conclusion, 2.5% ultrasound-assisted hydroethanolic solvent and pH 4.11-6.11 were the most suitable for extracting bioactive compounds from sugarcane molasses.